2019
DOI: 10.1186/s12888-019-2189-1
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of somatic symptoms by mental health and personality traits: application of Bayesian regularized quantile regression in a large population study

Abstract: Background Somatic syndrome is one of the remarkably prevalent issues in primary health care and subspecialty settings. We aimed to elucidate multidimensional associations between somatic symptoms with major mental problems and personality traits in the framework of the quantile regression model with a Bayesian approach. Methods A total of 4763 employees at Isfahan University of Medical Sciences and Health Services in Isfahan province, Iran, filled out four validated qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 37 publications
4
32
1
Order By: Relevance
“…Neuroticism positively correlated with stress, anxiety and depression. These results were also found by Vujičić and Ranđelović (2017) and Mostafaei et al (2019), and similar results were reported by other studies (Brailovskaia & Margraf, 2016;Ervasti et al, 2019;Gramstad et al, 2013;Milić et al, 2019;Mousavi & Essazadegan, 2016;Pereira-Morales et al, 2019;Seto et al, 2019;Sørengaard et al, 2019). In contrast, (A) negatively correlated with stress, anxiety and depression.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Neuroticism positively correlated with stress, anxiety and depression. These results were also found by Vujičić and Ranđelović (2017) and Mostafaei et al (2019), and similar results were reported by other studies (Brailovskaia & Margraf, 2016;Ervasti et al, 2019;Gramstad et al, 2013;Milić et al, 2019;Mousavi & Essazadegan, 2016;Pereira-Morales et al, 2019;Seto et al, 2019;Sørengaard et al, 2019). In contrast, (A) negatively correlated with stress, anxiety and depression.…”
Section: Resultssupporting
confidence: 90%
“…In contrast, (A) negatively correlated with stress, anxiety and depression. These correlations were reported by https: //doi.org/10.15405/epsbs.2020.05.17 Corresponding Author: Ana Moreno Selection and peer-review under 157 Mostafaei et al (2019). In the study by Vujičić and Ranđelović (2017) it was found the same results but it was not found the stress correlation.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Quantile regression by R software ( Mostafaei et al, 2019 ) was further applied to demonstrate whether the level of PIU was related to the association between PIU and engaged living. The results of quantile regression are shown in Figures 1A – C .…”
Section: Resultsmentioning
confidence: 99%
“…The participants were majorly involved in industries such as telecommunications, petroleum, and aeronautics. Stress analysis among banking employees was done across the countries from the Middle East to Africa [ 19 ]. It is also understood that job status is one of the prime reasons for getting stress.…”
Section: Related Workmentioning
confidence: 99%